Chemical Manipulation of Abscisic Acid Signaling: A New Approach to Abiotic and Biotic Stress Management in Agriculture. Issue 18 (7th August 2020) - Hewage, Kamalani Achala H.; Yang, Jing‐Fang; Wang, Di; Hao, Ge‐Fei; Yang, Guang‐Fu; Zhu, Jian‐Kang
Abstract: The phytohormone abscisic acid (ABA) is the best‐known stress signaling molecule in plants. ABA protects sessile land plants from biotic and abiotic stresses. The conserved pyrabactin resistance/pyrabactin resistance‐like/regulatory component of ABA receptors (PYR/PYL/RCAR) perceives ABA and triggers a cascade of signaling events. A thorough knowledge of the sequential steps of ABA signaling will be necessary for the development of chemicals that control plant stress responses. The core components of the ABA signaling pathway have been identified with adequate characterization. The information available concerning ABA biosynthesis, transport, perception, and metabolism has enabled detailed functional studies on how the protective ability of ABA in plants might be modified to increase plant resistance to stress. Some of the significant contributions to chemical manipulation include ABA biosynthesis inhibitors, and ABA receptor agonists and antagonists. Chemical manipulation of key control points in ABA signaling is important for abiotic and biotic stress management in agriculture. However, a comprehensive review of the current knowledge of chemical manipulation of ABA signaling is lacking. Here, a thorough analysis of recent reports on small‐molecule modulation of ABA signaling is provided. The challenges and prospects in the chemical manipulation of ABA signaling for the development of ABA‐based agrochemicals are also discussed. Abstract : Small molecules that can manipulate abscisic acid (ABA) signaling events are designed, developed, and evaluated. The ABA‐mediated stress adaptive responses of plants are mimicked by small molecules, and the ABA biosynthesis and catabolism events are altered by inhibitors. This approach is a novel way to gain chemical control over plant stress by using safer ABA‐based agrochemicals.